A Comparative Study of Natural Law Theories: The Views of Thomas F. Wall and Syed Muhammad Naquib al-Attas - Elvina Khoirun Nisa; Usmanul Khakim; Setiati Hamidah; Khasib Amrullah (Tasfiyah: Jurnal Pemikiran Islam, 2025)
This article aims to analyze and compare the perspectives of Thomas F. Wall and Syed Muhammad Naquib al-Attas on the concept of natural law, highlighting their differing philosophical traditions. Wall, in â€œCritical Thinkingâ€, presents a secular understanding of natural law, arguing that it is a human construct originating solely from human reasoning, independent of any divine authority. In contrast, al-Attas, in â€œProlegomena to the Metaphysics of Islamâ€, asserts that natural law, or sunnatullah, is divinely ordained, reflecting God's will in governing the universe while involving human participation. This study employs a philosophical approach grounded in the Islamic worldview to examine and contrast their interpretations, utilizing content analysis to systematically interpret the key arguments in their respective works. The findings reveal a fundamental divergence between the two perspectives: Wall perceives natural law as an innate principle recognized by human reason as the highest moral and ethical authority, whereas al-Attas views it as a manifestation of divine order that governs creation. This contrast underscores the broader epistemological differences between the Western secular and Islamic metaphysical worldviews in understanding the foundation and authority of natural law.